Students' anxiety in learning English writing in higher education - Iksan, Muhammad; Palangngan, Sukmawati Tono; Nur, Sahril (Journal of Applied Studies in Language, 2023)
Research studies on students' writing anxiety have been done in many EFL teaching contexts. However, there are still very limited scientific articles published about university students' foreign language writing anxiety and the causes in the Indonesian university context. Therefore, this study's main purpose was to analyze students' anxiety in EFL writing and its causes. This study employed a descriptive quantitative method. The study subjects were chosen from the first-year students of the Accounting Study Program of Muhammadiyah University of Palopo academic year 2021-2022, which consists of three classes. Two types of questionnaires were used for collecting the data. The first questionnaire was based on Second Language Writing Anxiety Inventory (SLWAI) developed by Cheng (2014). The questionnaire consisted of 21 items designed to assess students' English writing anxiety. The second questionnaire, the Second Language Writing Fear Inventory (CSLWFI), derived from Rezaei and Jafari's (2014), which was adopted to find out the causes of a feeling of anxiety in writing, consisted of ten questions. SPSS ver. 20 was used to analyze the gathered data. The findings revealed that the student's English writing anxiety was significant, and the key causes were poor understanding of writing concepts, linguistic obstacles, insufficient writing skill practice, and time restrictions.